IMPLEMENTATION OF THE 'START WITH A QUESTION' STRATEGY IN HISTORY LEARNING OUTCOMES FOR CLASS XI STUDENTS ATSMA NEGERI 3 KENDARI - Suharni Suddin (International Journal of Teaching and Learning, 2025)
This research employs an experimental design with test techniques, aiming to analyze descriptively and inferentially: (1) the influence of the "Start with a Question" learning strategy on the learning outcomes of class XI students at SMA Negeri 3 Kendari; (2) the influence of conventional learning strategies on the learning outcomes of class XI students at SMA Negeri 3 Kendari; (3) the differences in the influence on history learning outcomes between students taught using the "Start with a Question" learning strategy and those taught using conventional learning strategies. The population of this study consisted of all class XI students of SMA Negeri 3 Kendari, totaling 4 classes. The research sample was taken through multistage probability sampling, a form of random sampling of complex groups. This method considered that two classes had relatively similar abilities, sat in the same class, and were not divided based on student level. The experimental and control classes were determined randomly, with class XI.IS4 serving as the experimental class that implemented the "Start with a Question" learning strategy. Based on this perception, the researcher took 25% of the total population (more than 100) as a sample. The sample size in this study was 25% x 145 = 36. One reason for selecting a sample of 36 students was that each class included several students with poor attendance records. Data was collected through observation sheets and history test results, in multiple-choice format. The hypothesis was tested using a single sample t-test. If t count > > t(1-α,(n1+n2)-2) or P value < α, then H0 is accepted; otherwise, H0 is rejected. The results of the data analysis indicate that: (1) the history learning outcomes of students who applied the "Start with a Question" learning strategy were categorically very good, with 77.78% of students scoring between 80 and 100, and an average score of 83.96; (2) the history learning outcomes of students who applied conventional learning strategies were categorically moderate, with 72.22% of students scoring between 65 and 75, and an average score of 70.07; (3) the "Start with a Question" learning strategy positively influenced the learning outcomes on the material of Japanese colonialization and its impact on the lives of Indonesian people, with t = 10,575 = t(1-α; (n1+n2) -2) = t(0,95;70))), resulting in the rejection of H0.